CLASSIFICATION DATA EXPLORATION METHODS IN MODERN REALTIME DATA WAREHOUSE - Chłapiński, Jakub; Mazur, Piotr; Murlewski, Jan; Kamiński, Marek; Sakowicz, Bartosz (International Journal of Computing, 2014)
The goal of this article is to introduce problems that may arise during analysis of classification methods used in data mining applications. In the following sections some of the most common classification techniques are described along with several proposed extensions which allow these methods to be used in incremental data warehouses. The primary focus was aimed at the problem of performing incremental learning methods that may be used in near realtime data warehousing applications.